Improving Reading and Writing skills using an e-learning platform for eighth graders (2020)
This reading and writing online course proposal is designed to help eighth grade students who have shown a low performance in reading and writing English skills at Gimnasio Moderno Maria Auxiliadora School in Fusagasugá. The goal is to support students’ weakness and difficulties in reading and writing skills to improve their English language level. A need analysis based on reading and writing was carried out in class and some instruments were applied to determine students failed causes. Different classroom observations were followed out, and students’ attitudes to English Class were considered. A pre-test to measure student’s language level was applied. Some findings showed a significant lack of motivation towards language learning. Students showed special interest in digital activities, like games, or online challenges. An important necessity to increase and expand the use of technology in the classroom was detected. For mentioned reasons, an on-line improvement reading and writing course was designed. Some researchers’ guidelines for designing Effective E-learning English Teaching Materials were applied to design the course using “Chamilo LMS” e-learning platform.